Evaluación de los procedimientos de control interno bajo el método coso ii que permita identificar los riesgos de crédito de la cooperativa de ahorro y crédito Ambato ltda, de la provincia Tungurahua, en el periodo 2016-2017 - Caranqui Torres, Alex Fabricio (2018)
Internal Control is a fundamental element in each of the companies and public institutions if it is considered that it facilitates the efficient and integral control of the entire organization. This approach has its importance, in the sense that internal control is a set of procedures, policies, rules and organizational plans, which aim to ensure efficiency, security and order in the financial, accounting and administrative management of the company (safeguard of assets, fidelity of the information and registration process, compliance with defined policies). Financial entities are companies whose purpose is the acquisition, placement of financial resources of natural and legal persons, and the provision of services to their clients, which requires an optimum level of trust in internal control that allows the decrease in the level of credit risk. By virtue of the aforementioned, there is the concern to carry out an investigation, whose purpose will be to evaluate the internal control procedures under the Coso II method that allows to identify the credit risks of the Ambato Cooperativa de Ahorro y Crédito Ltda. Tungurahua province, in the period 2016-2017, so it is considered important and is a need for companies, the evaluation of these procedures as premises to enunciate and project solutions to strengthen internal control. From these perspectives, the research has as its fundamental purpose, to carry out an evaluation of the internal control from the Coso II method, from the identification of the dimensions and indicators of the level of confidence in internal control through Coso II as a variable, which allows designing a reliable and valid technique for conducting the diagnostic study in the Cooperative from a questionnaire that measures the key factors of the aforementioned method, preliminary internal control questionnaire, to perform a compliance test of critical areas from the verification of documentation and registration of evidences. Finally, an assessment of the level of confidence in internal control will be made to suggest proposals and alternatives that allow internal control to be strengthened.